Perdagangan Mekkah dan Kemunculan Islam (Mendiskusikan Tesis Montgomery Watt dan Patricia Crone) - Faisal Ismail (Al-Jami'ah Research Centre, 1999)
Montgomery watt and Patricia crone disagree about the important factors contributed to the rise of lslam in Mecea at the beginning of the seventh century. According to watt, it was the Meccan trade that became the main factor contributed to the rise of lslam. The transformation of social life in Arabia from nomadic to mercantile economy resulted in the collapse of social and moral values to which was Muhammad's response. In this case, Watt used a socioeconomic approach in understanding and explaining the rise of lslam. Different from watt, crone argued that the rise of lslam had nothing to do with the Meccan trade. According to crone, it was Muhammad's political mission that contributed to the rise of lslam. Muhammad struggled to promote Arab nationalism or Arab unity in his attempt to counterbalance the Byzantine and sasanid Empires, the two super powers dominated the Middle East at the time. so, crone's approach to the study of the rise of lslam was very political in nature. Despite some weaknesses, watt's theory of the rise of lslam was more generally accepted by Muslim historian than crone’s. In the view of Muslim historians, the socio-economic condition and political background of Arabia were not the main factors to explain the rise of Islam. The rise of lslam was strongly related to the implementation Muhammad's prophetic mission which put emphasis on the unity of God and equity of man.